Allelopathic effects of common vetch (Vicia sativa L.) on lettuce in laboratory tests - de Medeiros, Antônio Roberto Marchese; Lucchesi, Antonio Augusto (Pesquisa Agropecuaria Brasileira, 1993)
The allelopathic potential of Vicia sativa L. was determined by laboratory tests. Transparent plastic boxes containing humidified absorbent paper as a substrate were used. The laboratory parameter for determining the effects of the aqueous extracts on the substrate was the influence on the seeds, germination, on the length of the primary root and on the weight of lettuce (Lactuca sativa L.) seedlings. Effects of the different concentrations of aqueous extracts on the absorbent hairs formation were evaluated. Vicia sativa L. showed great influence on lettuce. In the highest concentrations of the aqueous extract (75% and 100%), seeds died and decayed rapidly.